Peran Guru Dalam Menerapkan Tata Tertib Peserta Didik Di Kelas IV SD Negeri 62 Banda Aceh - Ota Fitriansyah; sulaiman Sulaiman; Yamin M (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
This study aims to determine the teacher’s role in implementing student discipline in the classroom. This study uses a qualitative approach and the type of research used is descriptive. This study uses observation and interview techniques. The subjects in this study were three classroom teachers. Data processing is done through data reduction, data presentation, and drawing conclusions. Based on the observations, it is known that the fourth-grade teachers (A, B, C) have played a role in implementing student discipline in the classroom well. The role played by the teacher, such as educating students to be responsible for doing homework (PR), maintaining order in the classroom, providing direction to students so that they can complete assignments according to the allotted time, and guiding students to always look clean, getting students used to throwing garbage in its place, and will determine sanctions for students who violate the rules. Through the study results, it can be concluded that the three teachers have carried out their role in implementing the rules for students, but not all fourth-grade students have obeyed the rules well.